Pemenuhan Hak Pendidikan Bagi Penyandang Disabilitas Perspektif Hukum Nasional dan Hukum Islam - Hendra Dude; Fenty U. Puluhulawa; Nina Mirantie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2020)
This research discusses the fulfillment of the right to education for persons with disabilities. After the enactment of Law Number 8 of 2016, one of the government's obligations is to guarantee the right to education. This research is library research that is analyzed descriptively qualitatively with the approach of national law and Islamic law. The results showed that: first, Islamic law regulates equal rights in education without any distinction between physically normal people and people with disabilities. Likewise, national law has been regulated in Law Number 8 of 2016. However, this regulation needs to be followed up in the form of an implementing regulation to ensure that its compliance policies have a legal basis in the form of regional regulations. Second, the authority of local governments as stated in Law Number 23 of 2014 concerning Regional Government has mandated regions to administer education as a mandatory government affair related to basic services so that local governments in managing education must carry out their obligations to fulfill the right to education. to the community, especially for people with disabilities.